Between morality and discrimination by public administration: the case of so-called ‘LGBT free zones’ in Poland - Romańska, Marta; Cebera, Agata; Firlus, Jakub Grzegorz (Pécs journal of international and European law, 2023)
In recent years in Poland, local authorities were eager to express their views on ideological and moral issues. These statements were not mere declarations of a group of councilors (politicians) but administrative rule-making. The so-called LGBT-free zones have gained particular attention within the EU borders and abroad. These resolutions are of mixed i.e. normative and political characteristics. Moreover, the contribution seeks an answer to whether there is a legal basis for issuing such a resolution and whether it complies with EU law and the case law of the CJUE and ECHR. The analysis also covers a judicial review of resolutions issued by municipalities. Finally, it was described how the activities of the Polish accountability network contributed to a shift in EU policy regarding the protection of underrepresented groups.